2020
DOI: 10.1002/da.23062
|View full text |Cite
|
Sign up to set email alerts
|

Reduced hippocampal and amygdala volume as a mechanism underlying stress sensitization to depression following childhood trauma

Abstract: Background Stressful life events are more likely to trigger depression among individuals exposed to childhood adversity. However, the mechanisms underlying this stress sensitization remain largely unknown. Any such mechanism must be altered by childhood adversity and interact with recent stressful life events, magnifying their association with depression. Aim This study investigated whether reduced hippocampal and amygdala volume are potential mechanisms underlying stress sensitization following childhood viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 46 publications
2
50
2
1
Order By: Relevance
“…Smaller amygdalae (Edmiston et al, 2011;McLaughlin et al, 2016), as well as no differences, have been found in adolescents who experienced child maltreatment (De Bellis et al, 1999, 2002Carrion et al, 2001;Gold et al, 2016). Similarly, exposure to community violence during childhood was related to smaller amygdala volumes (Saxbe et al, 2018;Weissman et al, 2020); however, related recent work did not replicate this association in a similar sample (Butler et al, 2018).…”
Section: What Is the State-of-science Of Adversity's Impact Of The Amygdala? What Might Be Causing These Inconsistencies?mentioning
confidence: 93%
“…Smaller amygdalae (Edmiston et al, 2011;McLaughlin et al, 2016), as well as no differences, have been found in adolescents who experienced child maltreatment (De Bellis et al, 1999, 2002Carrion et al, 2001;Gold et al, 2016). Similarly, exposure to community violence during childhood was related to smaller amygdala volumes (Saxbe et al, 2018;Weissman et al, 2020); however, related recent work did not replicate this association in a similar sample (Butler et al, 2018).…”
Section: What Is the State-of-science Of Adversity's Impact Of The Amygdala? What Might Be Causing These Inconsistencies?mentioning
confidence: 93%
“…Thus, it is of major interest to compare HippSub volumes which might give us hints about common underlying mechanisms in affective disorders and AD. In depressive disorders, diverse mechanisms such as the number of depressive episodes, stressful life events, oxidative stress, childhood physical, or sexual abuse or metabolic changes are potential underlying mechanisms of lower HippSub volumes such as CA1 or dentate gyrus (DG) or fimbria (Treadway et al, 2015 ; Elvsåshagen et al, 2016 ; Xu et al, 2018 ; Weissman et al, 2020 ; Yuan et al, 2020 ). These studies depict that in depression, the mechanisms of hippocampal volume loss seem to be even broader than in hippocampal degeneration due to AD's spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Our study does not focus on specific HippSubs, as there is controversy about which HippSubs are reduced among different diseases. The intersection between lower HippSub volumes and various diseases associated with cognitive dysfunction is inconsistent in studies of AD's spectrum (Hanseeuw et al, 2011 ; La Joie et al, 2013 ; Carlesimo et al, 2015 ; de Flores et al, 2015 ; Cao et al, 2017 ; Szymkowicz et al, 2017 ; Jacobs et al, 2020 ), MDD (Treadway et al, 2015 ; Elvsåshagen et al, 2016 ; Xu et al, 2018 ; Weissman et al, 2020 ; Yuan et al, 2020 ), and BD (Cao et al, 2017 ; Haukvik et al, 2020 ). Therefore, we plan to take a more exploratory look at the volumes of various HippSubs.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this thought can be found in the literature; Dong et al found that childhood trauma was associated with psychological resilience, 28 while other studies showed that childhood trauma was related to depression 29 and suicidal ideation 30 and that it might indirectly confer vulnerability to stressful life events. 31 These results show that childhood trauma opposes three dimensions of psychological capital, namely, self-efficacy, hope, and optimism. Accordingly, we hypothesized that childhood trauma would have a negative effect on people’s psychological capital.…”
Section: Introductionmentioning
confidence: 88%